Extraction of pectin from sugar-beet pulp and intrinsic viscosity molecular weight relationship of pectin solutions - Arslan, N (Assn Food Scient Techn India, 1995)
Sugar-beet pulp pectin was extracted by using HCl (pH 1.5, 80 degrees C, 1 h), ammonium oxalate (0.25%, pH 3.5, 75 degrees C, 1 h) and EDTA (0.5%, 90 degrees C, 1 h). The best result was obtained with ammonium oxalate extraction in which the pectin content of the final product was 21.75%, although the efficiency among the procedure varied. The degree of methylation was higher than 50% in all pectin samples, indicating that the sugar-beet pectin is a high-methoxyl pectin. The degree of acetylation was high in all samples, indicating that the gelling capacity of sugar-beet pectin was poor. Magnitudes of intrinsic viscosity, and molecular weight of pectins obtained by extraction with HCl, ammonium oxalate, and EDTA were 110, 158, 208 ml/g and 41300, 30400, 15100, respectively. The data were fitted to Mark-Houwink-Sakurada equation as eta(1)=0.3 (M(w,ave))(0.613), which helped evaluate the average molecular weight of pectin solutions from sugar-beet with a knowledge of their intrinsic viscosity.
Keywords: sugar-beet pulp; waste; pectin; extraction; intrinsic viscosity; molecular weight